Novo enfoque no estudo da transição de fase composicional da solução sólida ferroelétrica (Pb,Ca)TiO3 - Lucena, Poty Rodrigues de (2006)
Ferroelectric materials have a vast application in modern industry as data storage devices. Some of this materials, as the ferroelectric oxides class ABO3, have phase transitions with the alteration of of the lattice modifiers concentration ("A"). The aim of this work was to study the tetragonal to cubic phase transition in (Pb,Ca)TiO3 ferroelectric solid solution with a experimental and theoretical view point. The powders and thin films were achieved by the polymeric precursor method and characterized by X ray diffraction, Raman spectroscopy, capacitance vs voltage and capacitance vs frequency electrical measurements on thin films. The theoretical results were obtained by periodic quantum-mechanical calculations of (Pb,Ca)TiO3 structure in discrete compositions, applying the density functional theory (DFT) for the calculations in CRYSTAL98r code. The comparison of theoretical and experimental results pointed that the solid solution starts from a ferroelectric tetragonal structure to a paraelectric cubic structure with the increase of calcium relative content and, albeit cubic in calcium concentrations above 40%, the perovskite structure conserve a local disorder of titanium atom in the perpendicular direction relative to the unit cell z axis. This local disorder was confirmed by the appearing of characteristics vibrational modes in Raman spectrum of the oxide powders of the higher symmetry. The theoretical results suggest that Ti-O bonds in the oxides posses a great influence in the unit cell electronic densities distribution. The X-ray diffraction profiles of (Pb,Ca)TiO3 reveal that the relative intensities of (hkl) plans of tetragonal structure obeys a first order exponential decay function with the increase of calcium concentration on the PbTiO3 structure. The ferroelectric experiments in thin films show a decrease of relative dielectric permittivity with calcium incorporation due the structural modifications imposed by alkaline cation increase. The thin films displayed formation of space charges, perceived in the degradation of capacitance vs voltage profile in low application frequencies of the reversal electric field.